Dictionary Of The Underworld (Wordsworth Collection) - Partridge, Eric (Wordsworth Editions Ltd, 1995)
This exotic compilation may be used both for inside information and to browse through for its mind boggling and often hilarious revelations from a world few explore at first hand.
Keywords: Americanisms; English Language